Research on marine environment and coral distribution on Nam Yet island using VNRedsat-1 and QuickBird images - Cuong, Do Huy; Nam, Le Dinh; Tung, Nguyen Xuan; Luan, Nguyen The; Anh, Bui Thi Bao; Nhan, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2019)
Based on the processing of VNRedsat-1 and QuickBird images in the area of Truong Sa archipelago, the research results showed the efficiency of assessing marine environmental characteristics in surroundings of these islands. In this paper, we presented the research results on Nam Yet island and adjacent area. The marine parameters in this research include sea surface temperature (SST) and chlorophyll-a concentration in the surface layer as well as in the deep layers of 20m and 40m, the distributions of the ground objects such as coral shelf, sand accumulation, coral reef combined with seagrass and seaweed. The accuracy of assessment of supervised and unsupervised classified results is approximate of 87.8%. The research results allowed assessing the environmental characteristics, warning of the risk of erosion and coastal line change in the study area.